Monitoring of hemodynamic indices in elite athletes in conditions of time zone offset - Povzun, V. D.; Povzun, A. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify changes in the central hemodynamic indices in highly-skilled athletes after a flight across several time zones.